Integration of CRISUS Weighting and ROV Method for Division Head Performance Evaluation in a Manufacturing Company - Junhai Wang; Setiawansyah Setiawansyah; Pritasari Palupiningsih (LPPM Universitas Bina Sarana Informatika, 2026)
The performance evaluation of division heads in manufacturing companies often faces various problems, such as high subjectivity in assessment, the absence of clear criteria weighting standards, and instability in ranking results due to data variation. This situation causes the evaluation results to be less consistent and less able to accurately represent performance. Therefore, this study aims to develop a more objective performance evaluation model by integrating the CRISUS and ROV methods. The CRISUS method is used to determine the criteria weights objectively based on the characteristics of data distribution, while the ROV method is used to rank alternatives by considering variations in performance values through upper and lower bound approaches. The criteria used include leadership, productivity, innovation, operational costs, and error rates. The research results indicate that the proposed model is able to produce more stable and consistent preference values in representing candidate performance. Based on the calculation results, CDT-03 obtained a preference value of 0.4316 and ranked first, followed by CDT-06 with a value of 0.4212 in second place, and CDT-01 in third place with a value of 0.3180. Meanwhile, CDT-02 was in the last position with a value of 0.0739. These findings show that the integration of the CRISUS and ROV methods is able to provide a more objective, comprehensive, and reliable evaluation in supporting managerial decision-making. This research provides several important contributions; this combination is able to overcome the weaknesses of conventional methods by presenting objective criteria weighting as well as a ranking mechanism that takes into account variations in performance conditions.